INCREASE OF SEISMOTECTONIC ACTIVITY IN THE BAIKAL REGION IN 1989-95: RESULTS OF EXPERIMENTAL OBSERVATIONS AND NUMERICAL MODELING OF CHANGES IN THE STRESS-STRAINED STATE - Djadkov P.G.; Mel'nikova V.I.; Nazarov L.A.; Nazarova L.A.; San'kov V.A. (My University, 1999)
Complex geophysical monitoring (seismological, tectonomagnetic, extensometric, and GPS observations) and numerical modeling were used to study the development of a seismotectonic process on the southwestern flank of the Baikal Rift Zone, including the central part of the Baikal basin, in 1989-95. In that period, 10 strong earthquakes (M = 5.6-6.5) occurred in the BRZ. The released seismic energy was two orders of magnitude greater than the energy released in the previous seven-year period. From 1992 till the middle of 1993, near-horizontal compression strains were predominant in the Baikal region. This follows from the presence of focal mechanisms of earthquakes with reverse-fault dislocations and the results of tectonomagnetic monitoring in the region of the Selenga basin and extensometric observations in the adit of the Talaya seismic station. These data and results of GPS observations started in 1994 evidence that extension strains were predominant in 1994-95. Numerical modeling of strain field changes by the method of finite elements has shown that a predominance of compression strains can be realized by specifying compressive loads across the strike of the Baikal basin and compensating extension stresses in this direction. Thus, the sources of compression strains should be located in the southeast or in the east and may be related to subduction processes at the convergent borders of Eurasia.